2008
DOI: 10.1111/j.1601-0825.2007.01394.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral and dental phenotype of dyskeratosis congenita

Abstract: Dyskeratosis congenita (DC) is an inherited bone marrow failure syndrome that is characterized by lacey reticular hyperpigmentation of the skin, dystrophic nails, mucous membrane leukoplakia and pancytopenia. Diagnosis may be delayed until clinical signs are apparent. Severe pancytopenia frequently causes early mortality of DC patients, who have an increased risk of developing oropharyngeal squamous cell carcinoma. Several case reports have described oral changes in DC, which include oral leukoplakia, increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 26 publications
(34 reference statements)
2
53
0
2
Order By: Relevance
“…In total, 65% of DC patients have oral leukoplakia, one symptom of the diagnostic triad. In addition, DC patients may have a decreased root/crown ratio, taurodontism, increased dental caries, hypodontia, thin enamel structure, periodontitis, tooth loss or blunted roots [60]. A study of the ocular manifestations of DC in the NCI cohort reported that 28% of DC patients have an obstructed lacrimal drainage system [61].…”
Section: Clinical Features Of DCmentioning
confidence: 99%
“…In total, 65% of DC patients have oral leukoplakia, one symptom of the diagnostic triad. In addition, DC patients may have a decreased root/crown ratio, taurodontism, increased dental caries, hypodontia, thin enamel structure, periodontitis, tooth loss or blunted roots [60]. A study of the ocular manifestations of DC in the NCI cohort reported that 28% of DC patients have an obstructed lacrimal drainage system [61].…”
Section: Clinical Features Of DCmentioning
confidence: 99%
“…It is mainly found in sun exposed areas of skin. Alopecia of scalp may be associated 7 . In our patient only few hyperpigmented macules were present over face and upper limb.…”
Section: Discussionmentioning
confidence: 99%
“…Mucosal leucoplakia occurs in approximately 80% of patients and typically involves the buccal mucosa, tongue, and oropharynx 7 . In our case leucoplakia was present over the tongue.…”
Section: Discussionmentioning
confidence: 99%
“…It's a multi-system disorder whose symptoms appear in childhood andleads to death between 16 and 50 years. DC occurs mainly in young male with a male to female ratio of 13/1 and mostly appears between 5 and 12 years [1][2]. This genetic affection is typically characterized by the association of a traditional dermatological triad: Reticular hyper pigmentation, nail dystrophy andleucoplakia of the mucous membranes.…”
Section: Introduction:-mentioning
confidence: 99%
“…DC has a poor prognosis, the current treatments remain non satisfactory. Mortality is often associated to severe pancytopenia, development of malignancy and other multisystem complications of the disease [2].…”
mentioning
confidence: 99%